PENERAPAN MEDIA PEMBELAJARAN GOOGLE SITES DALAM PEMBELAJARAN MAHARATUL KALAM SISWA KELAS VIII MTS N 2 KAB. POHUWATO - R. Yunus, Mohamad Ilham (Sekolah Tinggi Agama Islam (STAI) Al Hidayah Tasikmalaya, 2024)
The difficulty students face in learning Arabic, especially in the maharatul kalam (speaking skills), is not always due to the students themselves, but often because teachers may not fully understand the students' learning needs. A teacher should have the ability to address the challenges students face in learning. In response to this issue, technology emerges as one of the appropriate solutions. One technological product that contributes to education is the presence of learning media. Many studies have proven that learning media significantly aids students in their learning journey and makes it easier for teachers to teach. One such type of learning media is Google Sites. Therefore, this research aims to determine the results of implementing Google Sites as a learning media in teaching maharatul kalam to students in the Arabic language subject in class VIII at MTs N. 2 Kab. Pohuwato. The research method employed is the quantitative descriptive research method. Data collection techniques include interviews, observations, and questionnaires. The gathered data is analyzed using descriptive data analysis techniques. On this Google sites learning media, the learning media expert validator assigned a score of 4.4, indicating a very suitable level of feasibility. Similarly, the subject matter expert validator gave a score of 4.6, signifying a very suitable level of feasibility. As a result, this Google Sites learning media obtained an average score of 4.5, indicating a highly suitable level of feasibility for testing and implementation with students. Based on the questionnaires distributed to students via Google Forms, it can be concluded that approximately 75% of students provided positive responses. Thus, Google Sites learning media can be categorized as suitable for implementation.